Justification of specific principles of state and public management for sports area development in Ukraine - Volodymyr Prikhodko; Oleksandr Tomenko; Paweł Radziejowski; Nina Dolbysheva; Dmytro Solovey; Yaroslav Galan (Baltic Journal of Health and Physical Activity, 2021)
Background: The paper deals with the problem of sports area management improvement. The aim of the study is to substantiate the specific principles of state and public management, the application of which should be developed and implemented in the State Strategy of Ukraine in relation to high performance sports as a way of realization of the state policy. Methods: literature analysis, analysis of materials from the Internet, content analysis, generalization and analogy, expert evaluation and coefficient of Kendall’s concordance. Results of the study: The findings of content analysis of the Sports and Physical Activity of Ukraine until 2032 Development Strategy, which is used to justify the system of state and public management principles for the development of the sports sphere in Ukraine, are highlighted. The quality of the management principles system has been verified by using an expert evaluation (coefficient of Kendall’s concordance -0.82) Conclusion: Content analysis has specified the requirements for the content of the Sports and Physical Activity of Ukraine till 2032 Development Strategy. The system of principles is logically constituted by strategic, tactical and operational principles.